Redes sociais e intersetorialidade na gestão da saúde - Silva, Maria de Fátima da (2018)
This thesis aims to investigate the patterns of interactions in the intraorganizational and interorganizational relationship, as well as the intersectoral network, based on the analysis of the social networks among the managers that integrate the management team of health units and services of the Unified Health System (SUS) of the Municipality of São Paulo, a non-profit organization - SPDM. It was investigated if there is a process of interaction in social and intersectoral network in the management and between the units and health services of Ipiranga, Vila Mariana and Jabaquara and the other areas that work with the health area in meeting the demands of health users. The methodology of network analysis, of a quantitative nature, was carried out through the execution of an individual interview with the application of a form, to identify the existence of an interorganizational and interorganizational network and the intersectoral action, between sectors and organizations that interact with the health area. In the analysis of the data, the networks and the contact links among the agents, the subjects and shared themes were characterized, and the identification of the professionals demanded in these interactions, between the health units, health services and other organizations that interact with the Cheers. The data were entered in Excel and processed in the network analysis software, ORA.NetScenes. The metrics adopted allowed the identification and analysis of the structure of the network and the centrality of the agents in the interactions of the health area with the social assistance, education and services of the health care network, such as the relationship between Attention in Emergency and Emergency, Hospital Attention, Specialized Ambulatory Care and Psychosocial Care. The analyzes showed that the established links represent a small fraction of the total number of possible links between the health care modalities analyzed in the Ipiranga region and the Vila Mariana and Jabaquara regions. The regions denote high potential of development and strengthening intra-organizational relations between the modalities of attention in the integral care to the health user